Pengenalan Wadah Dan Sarana Budidaya Ikan Konsumsi Bagi Siswa Kelas IX SMP Sitanala Learning Center Ambon - Sophia N.M. Fendjalang; Krisye Krisye (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
One form of environmental education that can be implemented in schools is through introducing the concept of fish farming to school students. Presenting the concept of fish farming to middle school students has the advantage of providing a deep understanding of biodiversity, the aquatic environment, responsibilities and practical skills. One form of holistic education developed at Sitanala Learning Center Middle School is a craft on cultivating food fish. The Aquaculture Department, Faculty of Fisheries and Marine Sciences, Pattimura University has the opportunity to collaborate with the Sitanala Learning Center Middle School in sharing knowledge related to the introduction of aquaculture in early childhood. PkM activities will be held on Tuesday, October 24 2023 at 07.15 WIT - finished in class IX SMP Sitanala Learning Center Ambon. This activity consists of several stages, including; preparation, technical preparation, implementation, and implementation and evaluation of activities. The conclusion from the community service activities in the form of delivering material about containers and facilities for cultivating food fish to students at Sitanala Learning Center Middle School is that introducing cultivation activities to children is an interesting experience and can increase their understanding of cultivating food fish.